Objective Reconstructions of the Late Wisconsinan Laurentide Ice Sheet and the Significance of Deformable Beds - Fisher, D.; Reeh, N.; Langley, K. (Géographie physique et Quaternaire, 1985)
ABSTRACTA three dimensional steady state plastic ice model; the present surface topography (on a 50 km grid); a recent concensus of the Late Wisconsinan maximum margin (PREST, 1984); and a simple map of ice yield stress are used to model the Laurentide Ice Sheet. A multi-domed, asymmetric reconstruction is computed without prior assumptions about flow lines. The effects of possible deforming beds are modelled by using the very low yield stress values suggested by MATHEWS (1974). Because of low yield stress (deforming beds) the model generates thin ice on the Prairies, Great Lakes area and, in one case, over Hudson Bay. Introduction of low yield stress (deformabie) regions also produces low surface slopes and abrupt ice flow direction changes. In certain circumstances large ice streams are generated along the boundaries between normal yield stress (non-deformable beds) and low yield stress ice (deformabie beds). Computer models are discussed in reference to the geologically-based reconstructions of SHILTS (1980) and DYKE ef al. (1982).